Dynamic response and damage evolution characteristics of uniform rocky slopes with unstable rock masses based on shaking table tests - Wang, Dong; Wen, Hao (Frontiers in Earth Science, 2025)
Seismic activities often trigger catastrophic events including collapses and rockfalls on rocky slopes. This research endeavors to understand the dynamic behavior and damage modes in uniform rocky slopes with unstable rock masses. To achieve this objective, the paper constructs a physical model of uniform rocky slope with unstable rock mass and performs triaxial loading shaking table tests. Subsequently, the seismo-dynamic responses and associated damage modes of the slope are scrutinized, and the initiation and deformation mechanisms of the hazardous rock are revealed. Further, we obtained the marginal spectral energy evolution characteristics of measurement points of both the unstable rock and bedrock. This deciphers the damage evolution characteristics of the weak structural plane. The results indicate that there are distinct elevation and surface amplification effects within the rock slopes, which systematically lessened with increasing seismic intensity. The vertical deformation of unstable rock mass is more sensitive to high seismic intensity. The seismic-induced initiation process of unstable rock masses is split into three stages: trailing edge tension cracking, sliding damage of structural planes, and a complete failure of structural plane shear capacity. It is also established that the Hilbert and marginal spectra effectively identified the damage process of unstable rock masses containing weak structural planes.